Coherency Work-life Balance, Compensation, Job Satisfaction and Organizational Commitments Millennial Generations - Elpariani, Ni Putu Laras Alda Risma; Riana, I Gede; Surya, Ida Bagus Ketut (Global Journal of Social Sciences Studies, 2020)
The term millennial generation is being heard, often called generation me or echo boomers. There is no specific demographic in determining this generation group. Millennial generation is a generation between 20-36 years old. One of the problems of the millennial generation in the workplace is the low level of organizational commitment due to environmental influences at work, such as work-life balance, compensation, and job satisfaction. However, if you are able to manage the millennial generation, it can be more beneficial for organizations because they tend to be more creative. This study aims to analyze the effect of work-life balance, compensation, and job satisfaction on organizational commitment. Conducted on front liner employees at Hotel Melia Bali with a sample size of 65 respondents. The collected data were analyzed using multiple linear regression. The results show that work-life balance, compensation, and job satisfaction can significantly increase organizational commitment of millennial generation employees. Implication of this research also informs that increasing organizational commitment can be done by providing flexibility in working time, setting clearer reward standards and implementing transparent employee promotions.